Anthrax Vaccine and the Risk of Rheumatoid Arthritis and Systemic Lupus Erythematosus in the U.S. Military: A Case–Control Study. Issue 10 (1st October 2016) - Bardenheier, Barbara H.; Duffy, Jonathan; Duderstadt, Susan K.; Higgs, Jay B.; Keith, Michael P.; Papadopoulos, Patricia J.; Gilliland, William R.; McNeil, Michael M.
ABSTRACT: U.S. military personnel assigned to areas deemed to be at high risk for anthrax attack receive Anthrax Vaccine Adsorbed (AVA). Few cases of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) have been reported in persons who received AVA. Using a matched case–control study design, we assessed the relationship of RA and SLE with AVA vaccination using the Defense Medical Surveillance System. We identified potential cases using International Classification of Diseases, 9th Revision, Clinical Modification codes and confirmed cases with medical record review and rheumatologist adjudication. Using conditional logistic regression, we estimated odds ratios (OR) for AVA exposure during time intervals ranging from 90 to 1, 095 days before disease onset. Among 77 RA cases, 13 (17%) had ever received AVA. RA cases were no more likely than controls to have received AVA when looking back 1, 095 days (OR: 1.03; 95% confidence interval [CI]: 0.48–2.19) but had greater odds of exposure in the prior 90 days (OR: 3.93; 95% CI: 1.08–14.27). Among the 39 SLE cases, 5 (13%) had ever received AVA; no significant difference in receipt of AVA was found when compared with controls (OR: 0.91; 95% CI: 0.26–3.25). AVA was associated with recent onset RA, but did not increase the risk of developing RA in the long term.